Estimating habitat loss due to wind turbine avoidance by bats: Implications for European siting guidance. (October 2018) - Barré, Kévin; Le Viol, Isabelle; Bas, Yves; Julliard, Romain; Kerbiriou, Christian
Abstract: Wind energy is rapidly growing as a renewable source of energy but is not neutral for wildlife, especially bats. Whereas most studies have focused on bat mortality through collision, very few have quantified the loss of habitat use resulting from the potential negative impact of wind turbines, and none of them for hub heights higher than 55 m. Such impacts could durably affect populations, creating a need for improvement of knowledge to integrate this concern in implementation strategies. We quantified the impact of wind turbines at different distances on the activity of 11 bat taxa and 2 guilds. We compared bat activity at hedgerows (207 sites) located at a distance of 0–1000 m from wind turbines ( n = 151) of 29 wind farms in an agricultural region in the autumn (overall 193, 980 bat passes) using GLMMs. We found a significant negative effect of proximity to turbines on activity for 3 species ( Barbastella barbastellus, Nyctalus leisleiri, Pipistrellus pipistrellus ), 2 species-groups ( Myotis spp., Plecotus spp.) and 2 guilds (fast-flying and gleaner). Bat activity within 1000 m of wind turbines by gleaners and fast-flying bats is reduced by 53.8% and 19.6%, respectively. Our study highlighted that European recommendations (at least 200 m from any wooded edge) to limit mortality events likely strongly underestimate the loss of bat activity. The current situation is particularly worrying, with 89% of 909 turbines established in a region that does not comply with recommendations, which themselves are far from sufficient to limit the loss of habitat use. Highlights: High negative effect on bat activity of proximity to wind turbines for some species Some of these species were so far unknown to be impacted by wind turbines. Activity of gleaners and fast-flying bats close to turbines is reduced by 53.8% and 19.6%. The impact occurs over 1000 m around wind turbines. European recommendations are unapplied and far from sufficient for this impact.